Effects of board game on speaking ability of low-proficiency ESL learners - Yong, Mei Fung; Yeo, Li Min (Australian International Academic Centre, 2016)
ESL learners often experience anxiety and feel uncomfortable when speaking in the target language. This paper examines the anxiety level of polytechnic students when speaking English and the effects of board game on their speaking performance. The participants were selected from two intact classes which were randomly assigned into experimental and control groups comprising 30 students each. Data were obtained from pre- and post-treatment speaking tests and questionnaire. The questionnaire measuring anxiety factors was adapted from Yaikhong and Usaha (2012) and Woodrow (2006). The board game “What Say You” employed during the treatment was a speaking activity which required players to speak on a topic within a given time frame. The experimental group played the board games over six sessions. The results from the experimental and control groups showed significant difference in the pre- and post-treatment speaking test scores. However, the speaking performance of the experimental group revealed significantly higher scores. Students who were initially hesitant and passive were more willing to speak and were able to present and justify their ideas more confidently as compared to the control group after the treatment. The findings reveal that the board game is a useful tool to engage learners’ participation in class and to enhance the speaking ability of low-proficiency ESL learners.